Implementasi Balanced Scorecard sebagai Alat Evaluasi Kinerja Strategis dalam Era Transformasi Digital - Nasrullah Nasrullah; Romansyah Sahabuddin; Rahmatullah Rahmatullah; Abdul Rahim (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the implementation of the Balanced Scorecard (BSC) as a strategic performance evaluation tool in the era of digital transformation. Using a descriptive qualitative approach within the social constructivist paradigm, data were collected through in-depth interviews, non-participant observation, and document analysis in three organizations undergoing digitalization. Thematic analysis (Braun & Clarke, 2006) identified four main themes in the application of the BSC: digital strategy alignment, digital readiness and data integration, a culture of learning and innovation, and adaptive leadership transformation. The findings indicate that the BSC functions not only as a performance measurement system but also as an adaptive, collaborative, and data-driven strategic management framework. The integration of digital technologies accelerates decision-making processes and strengthens reflective organizational culture. Theoretically, this study extends the classical BSC model of Kaplan and Norton (1996, 2001) toward a Digital Balanced Scorecard that emphasizes synergy among strategy, data, and organizational learning. Practically, the results highlight the importance of digital readiness, an innovation-oriented culture, and adaptive leadership as key foundations for successful BSC implementation in the era of digital disruption.